Physiological and biomechanical aspects of force production can be used in the training control of elite rowers - Baptista, R. R.; dos Santos Cunha, G.; Reischak de Oliveira, A. (Revista Brasileira de Medicina do Esporte, 2008)
The sports science currently requires approaches that match the study of biomechanical and physiological aspects, for the correct understanding of the phenomena related to human performance. The aim of this study was to investigate the differences in biomechanical and physiological responses between different force-time curves in rowers. Fifteen rowers (23.6 ±5.4 yrs), were submitted to maximal rowing ergometer. The biomechanical (peak force, power and impulse) and physiological (VO2, VCO2, VE, RER MET, lactate and HR) responses were measured in the lactate threshold stage as well as in the maximal stage reached by the rowers. The rowers were classified in two groups according to the localization of the peak force in their force-time curves: peak force in the first half of the curve (stroke) or in the second half of the curve (bow). There are no significant differences between the parameters measured in the two groups at lactate threshold stage of the rowing ergometer. Twelve rowers presented finish accentuated force curve in the lactate threshold; however, five (41.7%) changed for a catch accentuated pattern, while seven (58.3%) kept the original force-time profile in the maximal stage of the rowing ergometer. The rowers with a finish accentuated profile showed higher power production (p<0.05). The results suggest that coaches interested in extending exercise time must seek a finish accentuated force-time profile. Catch accentuated rowers could be better adapted to faster boats.